TEACHING PRONUNCIATION BY USING GAMES AND AUDIO VISUAL MEDIA - Erisa Kurniati (Universitas Negeri Padang, 2016)
Pronunciation is important in English as communication purpose because, if we mispronounce a word, it will lead into misunderstanding. Pronunciation is how the way we pronounce the word. Unfortunately, some English learners think that basic vocabulary and grammar are enough for communicative with English native speaker, but they are wrong. We need to pronounce well so people can understand what we are talking about. Audio visual media is one of media that can be used as the tool in learning and teaching process, but it is not enough to make the students interest in class, teacher need something special here. One of the way that teacher can use is game. There are so many kinds of games and teacher can combine it with audio visual media. This combination can create an interactive class. This article is about Teaching Pronunciation by Using Games and Audio Visual Media, to know how to used games and audio visual media then combine it in learning. It is important because by using games and audio visual media in fact are able to create fun and relax situation of the students in learning process, the students more able to answer teacher’s questions and more active to give suggestion to the teacher. They will not refuse to read dialogue in front of the class, cheerful, pay attention to the learning, and active during the teaching and learning process.